Ligand-induced activation of human TRPM2 requires the terminal ribose of ADPR and involves Arg1433 and Tyr1349 - Fliegert, Ralf; Watt, Joanna M; Schöbel, Anja; Rozewitz, Monika D; Moreau, Christelle; Kirchberger, Tanja; Thomas, Mark P; Sick, Wiebke; Araujo, Andrea C; Harneit, Angelika; Potter, Barry V L; Guse, Andreas H (Biochemical journal, 2017)
TRPM2 (transient receptor potential channel, subfamily melastatin, member 2) is a Ca -permeable non-selective cation channel activated by the binding of adenosine 5'-diphosphoribose (ADPR) to its cytoplasmic NUDT9H domain (NUDT9 homology domain). Activation of TRPM2 by ADPR downstream of oxidative stress has been implicated in the pathogenesis of many human diseases, rendering TRPM2 an attractive novel target for pharmacological intervention. However, the structural basis underlying this activation is largely unknown. Since ADP (adenosine 5'-diphosphate) alone did not activate or antagonize the channel, we used a chemical biology approach employing synthetic analogues to focus on the role of the ADPR terminal ribose. All novel ADPR derivatives modified in the terminal ribose, including that with the seemingly minor change of methylating the anomeric-OH, abolished agonist activity at TRPM2. Antagonist activity improved as the terminal substituent increasingly resembled the natural ribose, indicating that gating by ADPR might require specific interactions between hydroxyl groups of the terminal ribose and the NUDT9H domain. By mutating amino acid residues of the NUDT9H domain, predicted by modelling and docking to interact with the terminal ribose, we demonstrate that abrogating hydrogen bonding of the amino acids Arg1433 and Tyr1349 interferes with activation of the channel by ADPR. Taken together, using the complementary experimental approaches of chemical modification of the ligand and site-directed mutagenesis of TRPM2, we demonstrate that channel activation critically depends on hydrogen bonding of Arg1433 and Tyr1349 with the terminal ribose. Our findings allow for a more rational design of novel TRPM2 antagonists that may ultimately lead to compounds of therapeutic potential.